ANALISIS FENOLIK DAN FLAVONOID DALAM EKSTRAK METANOL DAUN SUNGKAI (Peronema canescens Jack.) SECARA SPEKTROFOTOMETRI - Nofita, Dewi; Setiawan, Budi; Marthia, Cut Mina; Putri, Desi Eka (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
Sungkai (Peronema canescens Jack.) is an indigenous Indonesian plant traditionally used for the treatment of fever, enhancing immune function, and managing hypertension. This study aimed to determine the total phenolic and flavonoid contents of methanol extracts of Sungkai leaves using spectrophotometric analysis. Phenolic content was measured using the Folin–Ciocalteu reagent with gallic acid as the standard, while flavonoid content was quantified using quercetin as the reference compound. The results showed that the methanol extract of Sungkai leaves contained a total phenolic content of 255.760 ± 0.0146 mg GAE/g extract and a total flavonoid content of 52.014 ± 0.0301 mg QE/g extract. These findings indicate that Sungkai leaves represent a promising natural source of bioactive metabolites with potential health benefits.